Peace Journalism and News Coverage on Cyprus Conflict in Cyprus Newspapers - Ersoy, Metin (My University, 2008)
Peace journalism is a new concept in the academic area and media sector. Although, there are several attempts to establish a global approach to peace journalism, we have to be careful in adapting them to local conditions. It is important to stress that peace journalism is a new kind of reporting, news selecting and news framing for the journalism profession. At the start of the 21st century, Galtung (1998, 2002), Kempf (1996, 2002), Shinar (2003), and others (see, e.g., Austrian Study Center for Peace and Conflict Resolution, 2003; Lynch & McGoldrick, 2005) advocated creative models and training programs … to transform the role of media (cited in Ross, 2006, p. 4). The most prominent peace researcher Johan Galtung first began using the term ‘Peace Journalism’ in the 1970s. Galtung (2002) defines peace journalism as such: “Peace journalism stands for truth as opposed to propaganda and lies, “truthful journalism” being, as mentioned, one aspect in peace journalism. It is not “investigative journalism” in the sense of only uncovering lies on “our” side. The truth aspect in peace journalism holds for all sides, just like exploration of the conflict formation and giving voice (glasnost) to all (p. 5).” Galtung (2002) stresses the “truth oriented” sides of peace journalism; some scholars make similar description for peace journalism. For instance, Shinar (2006) defines peace journalism as a “good journalism”, Lych and McGoldrick (2005) call “accurate journalism”, “post realistic journalism” and “Conflict analysis journalism”, Kempf (2003) labels “de-escalation oriented conflict reporting”, or Bandakov (2006) and Shinar (2007a) entitle “responsible journalism”. Lynch and McGoldrick (2005) define peace journalism as quality journalism that uses a creative set of tools to include routinely or habitually under-represented perspectives to provide deeper and broader coverage of news (pp. 5, 224). Galtung (2002) also supports Lynch and McGoldrick’s (2005) views on peace journalism; according to Galtung (2002) “peace journalism gives a more realistic image of what goes on in the world (p. 5)”. One can know from Gatekeeping Theory, some news events are not reported by a journalist or are not selected by editors which mean peace journalism tries to present the uncovered issues. In this paper, I present the results of an investigation on news coverage of the Cyprus Conflict and how Turkish and Greek Cypriot press are covering the “other side”. In order to find out the news coverage of Cyprus Conflict a ‘Content Analysis Coding Schema’ has been developed. In this ‘Content Analysis Coding Schema’, there are 16 questions that are related to the coverage; evaluation of the headline, quoted sources in the story, topic of news article, framing of the news, and some other technical information such as page number, size of the news, date etc. ‘Content Analysis Coding Schema’ will also address these issues; How Turkish/Greek Cypriot journalists select headlines [positive, natural, negative], who writes the articles [source of the article] what are the main news topics? The samples for this research study were publications in May 2006. The ‘Content Analysis Coding Schema’ was conducted on news articles which related with the Cyprus Conflict, Turkey, Greece, and Turkish and Greek Cypriots. The selected items ranged between; 1110 news items from the Turkish Cypriot newspapers and 309 news items from the Greek Cypriot newspapers. Five Turkish and five Greek Cypriot newspapers were selected as samples for this study, in order to analyze Turkish/Greek Cypriot press coverage of the Cyprus Conflict. The Greek Cypriot newspapers are Alithia, Haravghi, Phileleftheros, Simerini and Politis; the Turkish Cypriot papers are Kibris, Afrika, Yeni Duzen, Halkin Sesi and Volkan. Regarding Greek Cypriot newspapers; Alithia, has close relationship with DISI, the main opposition party. Alithia opposes governmental policies and supports unification initiatives. Alithia can be described as a liberal newspaper. Haravghi on the other hand, is owned by AKEL, the communist party now in the government and has been opposed to the Annan Plan referendum campaign. Phileleftheros, is a commercial newspaper with the highest circulation in the South. Politis is an independent newspaper and it has the second highest circulation, supporting peace initiatives with columnist contributors from Turkish Cypriots. Simerini, can be described as a fanatic rightwing newspaper. The editorial policy of the Simerini newspaper is following the EOKA-B line. For the Turkish Cypriot newspapers, the following comments can be made; Kibris, has the highest circulation in the North, it is highly influential, and it supports peace initiatives. Afrika, is an opposition paper in the North, and withstands an active stand on the Cyprus problem with columnist contributors from Greek Cypriots. Yeniduzen, is owned by the Republican Turkish Party now in government of the TRNC, and it supports unification of the island. Volkan, is an opposition paper, nationalist in ideology, and does not support unification. Halkin Sesi, is the oldest Turkish language newspaper on the island, privately owned and can be described as a rightwing newspaper. In summary, this paper will expose the reader to the news coverage of the Cyprus Conflict practices and principles of the thus far unknown Cyprus news media and its contribution positive/negative to the ongoing peace process in the Cyprus problem.
Keywords: Peace Journalism; news media; Cyprus Conflict; news framing; role of the media; public opinion